Perception of medical interns about simulation-integrated curriculum of their emergency medicine rotation - Alsulimani, Loui Kamel (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the perception of interns about their experience during one-month rotation in the emergency department, and the impact of adding simulation-based training. Method: The retrospective study was conducted at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, and comprised feedback surveys filled by interns at the end of their rotation in the emergency department between December 2017 and July 2020. The feedback questionnaire in use is aimed at evaluating interns’ experience with the emergency department rotation and the common academic activities during the rotation period. A comparison was done between those who had received simulation-based training and those who had not. Data was analysed using SPSS 24. Results: Of the 971 interns having done rotation in the emergency department, 718(74%) had completed the survey. Simulation-based training had been received by 208(29%) interns, while 510(71%) had not received it. Mean points given on a scale of 1-10 by the interns was 8.2+/-1.8. Overall, 684(95%) interns believed the rotation had met or exceeded their expectations (p>0.001). There was no significant difference between those who had received simulation-based training and those who had not (p>0.05). Conclusion: Interns had a positive perception towards the learning experience during their emergency department rotation, but there was no difference between those who had received simulation-based training and those who had not. Key Words: Simulation, Internship, Emergency medicine, Curriculum, Education.